1985
DOI: 10.1093/nar/13.4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of a complete ribosomal spacer ofD. melanogaster

Abstract: We determined the nucleotide sequence of a D. melanogaster ribosomal DNA spacer. Sequences of various portions of different cloned ribosomal spacers have been previously reported. We extend the analysis to cover the entire nontranscribed and external transcribed regions. Comparison to other cloned ribosomal DNA gene units of this species confirms a conserved general organization of the ribosomal spacer through different size classes. D. melanogaster ribosomal gene units interrupted by insertions are known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…In Xenopus, arrays of enhancer-like sequences (60/81-bp elements) are interspersed within the NTS with copies of the pre-rRNA promoter (9-12). While the 60/81-bp elements alone are able to stimulate the activity of the pre-rRNA promoter (10-12), transcription from the duplicated promoters is required for full spacer enhancement (13)(14).Multiple copies of the promoter region are found in the NTSs ofDrosophila melanogaster (15)(16)(17)(18)(19), Drosophila virilis (20, 21), Drosophila orena, and Drosophila hydeii (21) rDNA. We have shown (22) Fig.…”
mentioning
confidence: 99%
“…In Xenopus, arrays of enhancer-like sequences (60/81-bp elements) are interspersed within the NTS with copies of the pre-rRNA promoter (9-12). While the 60/81-bp elements alone are able to stimulate the activity of the pre-rRNA promoter (10-12), transcription from the duplicated promoters is required for full spacer enhancement (13)(14).Multiple copies of the promoter region are found in the NTSs ofDrosophila melanogaster (15)(16)(17)(18)(19), Drosophila virilis (20, 21), Drosophila orena, and Drosophila hydeii (21) rDNA. We have shown (22) Fig.…”
mentioning
confidence: 99%
“…A sequence comparison of rDNA transcription units of different eucaryotes reveals conservation of this termination signal sequence in rat DNA (2,22). A 10-bp repeated sequence with an 8-bp perfect homology to the mouse Sall box is found in the human NTS (14), and no significant homology is observed in lower eucaryotes (11,13,18). Thus (13,20).…”
Section: Discussionmentioning
confidence: 98%
“…fluminensis is also unusual for having large repeats. Large repeats of varying size have been reported in the rDNA spacers of species in the genera Daphnia, Aedes, Drosophila, Rattus, and Xenopus (Labhart and Reeder 1984, Simeone et al 1985, Murtif and Rae 1985, Cassidy et al 1986, Park and Fallon 1990, Crease 1993. Perera et al (1998) also reported a 36-nucleotide repeat in the intergenic spacer of Anopheles aquasalis Curry.…”
Section: Discussionmentioning
confidence: 99%